Altered cytokine and chemokine profile linked to autoantibody and pathogen reactivity in mothers of autistic children - McLellan, Janna; Croen, Lisa; Iosif, Ana-Maria; Yoshida, Cathleen; Ashwood, Paul; Yolken, Robert H.; Van de Water, Judy (Frontiers in Psychiatry, 2024)
Maternal autoimmunity, and more specifically, the production of specific maternal autoantibodies, has been associated with altered offspring neurodevelopment. Maternal autoantibody-related (MAR) autism is a subtype of autism that is linked to gestational exposure to certain combinations of autoantibodies known to be important for fetal neurodevelopment. We wanted to address whether mothers with autism-specific patterns of autoantibodies have a skewed cytokine and chemokine profile during an immune response to infection. To do so, we examined a subset of mothers from the Early Markers for Autism (EMA) study who either produced known patterns of MAR autoantibodies (MAR+) or did not (MAR-). We compared the cytokine/chemokine profiles of MAR+ and MAR-mothers in the context of positive immunoglobulin G (IgG) reactivity to several viral and parasitic agents. We observed that MAR+ mothers have a higher level of proinflammatory cytokine interferon-gamma regardless of IgG status. Additionally, when comparing MAR+ and MAR-mothers in the context of the different pathogens, MAR+ mothers consistently had increases in multiple proinflammatory cytokines and chemokines. * Group differences remained significant after correcting for multiple comparisons using false discovery rate.